STUDY ON KINEMATICS AND SINGULAR POSITION OF A 5-AXIS MACHINE TOOL - LAI Xiao (Jixie qiangdu)
According to the AC-type five-axis machine used in Lab,the kinematic matrix transformation of the five-axis coordinate is analyzed,and the mathematical relation between the tool axis vector and the angle of the rotation table is finally obtained. Then the inverse kinematics equation is established to realize the conversion of machine coordinates and programming coordinates operation. The corresponding post-processing program has been developed. The angle of the C-axis during the rotating shaft is greatly changed at the singularity configuration,which may exceed the system performance limit and lead to quality problems such as gouge on the surface of the workpiece. A method is proposed that the Cutter Location data could be adjusted to avoid the singular position by interpolation. VERICUT simulation of the tool path for the S surface is carried out,and the C-axis angle is actually reduced at the singular point,which verifies the correctness of the inverse kinematics equation and the feasibility of the proposed method.